Novos ares, nova vida: mobilidade, casamento e família nos sertões do Siará Grande (1759-1766) - Pinheiro, Adson Rodrigo Silva (2016)
The objective of this text is made a analysis of some bigame relationships, this cases were target of inquisitorial activity, this paper have the purpose to study the relationships and social interactives in the Siará of the XVIII century, in this society we have important themes like the high mobility of the people, the personal significancy of the marriage , the change of identity and profession, beloynd the acting of the church. In this text we want to understand how the people seen the marriage, what their motivations and strategies to marry for the second time, contradicting the Catholic Church, once the first wife, in some cases was alive. Others objectives of this study are understand how the Catholic Church did the analysis of this bigame cases acting in the population control. The documental basis os this study it is made of Inquisitorial Processes, this documents is in the Tombo Tower Archive, Inquisitorial Ordinance, First Archbishopric Constitutions of Bahia, Chapters of the Visitors Book of the Tombo of the cities of Russas and Arneiroz and Ordinations of the Kingdom. Our conclusion is that the study of bigame cases is possible understand the marriage values to the people and to the control institutions.